Asymmetrical cross–linguistic semantic activation in Portuguese–English–Chinese trilinguals: evidence from masked translation priming - Yu, Lishen; Kong, Qingqing (Frontiers in Psychology, 2026)
Research on multilingual semantic representation has largely focused on Indo-European languages, with limited evidence from typologically distant systems. The present study examines Portuguese–English–Chinese trilinguals using a masked translation priming paradigm to investigate whether semantic activation is directionally asymmetrical and how language distance and status influence trilingual processing. Fifty-nine participants completed an animacy judgment task involving 72 non-cognate translation triplets. Reaction times were analyzed with generalized linear mixed-effects models. Results showed significant priming only in the Portuguese → English and English→Chinese directions, while no reliable effects were found in other pairings, including Portuguese ↔ Chinese. These findings suggest that typological distance constrains cross-linguistic activation, whereas L2 can mediate activation toward L3 under conditions of higher proficiency and instructional use. The study highlights typological distance and L2 status as joint determinants of trilingual semantic representation and underscores the need to refine multilingual processing models beyond Indo-European contexts.